Técnicas e instrumentos de evaluación en el mejoramiento de la calidad de los aprendizajes en el área de ciencias naturales de los niños y niñas de séptimo año de educación básica de la escuela Gabriela Mistral del cantón Chillanes , provincia Bolívar en el periodo lectivo 2011-2012”. - García Aguilar, Blanca España (2012)
The present work leaves from the necessity fundamental to count on instruments and techniques of evaluation that allow qualitatively to value the learnings reached about the students of the school and which they will serve like referring for the improvement of these learnings. By such reason, the work is developed in several chapters; that in his first part talks about the subject, the antecedents, the problem, the justification, objective, general as as much specific, hypothesis, variables and the operacionalización of variables. In the first chapter the theoretical fundamentación of the work, constituted by the scientific theory is shaped, in that the two variables are developed, the one that concerns to instruments and techniques of evaluation, its characteristics, importance and utility;as well as the quality of the learnings that are due to reach with the children and children of the school. The second chapter talks about to the applied methodologic strategies for the development of the work, where the types of investigation are considered, the universe and shows to be investigated, as well as the methods for the work and the techniques for the investigation. In which it concerns to the third chapter, there the analysis of the results obtained through the investigation of field is carried out; with results organized in the statistical table, and represented in the bar charts, and foot it is the analysis of each carried out question to the students of the school Gabriela Mistral. As far as the fourth chapter, he is the one that contains the proposal, like an alternative with which one looks for to solve the problem detected through the investigation and that in our case, talk about the evaluation of the learnings. XII